Caracterização do perfil de ingresso de serviços de ligação nova sem obra após a execução de corte comercial em concessionárias de distribuição de energia elétrica - Conte, Marcelo (2018)
Electricity distribution companies have the purpose of providing reliable energy supply for its customers, fulfilling regulatory performance metrics. This paper aims to identify time profile incoming of customers’ requests, with focus on services of new connections requested by clients that were disconnected because of debt. To build a classification model for estimating new services requests is an essential conditional for a distribution company productive planning, measuring short time work hours necessities. It will be selected a city with huge commercial demands, displaying how challenging it is for a distribution company to perform processes metrics in accordance with regulatory expectations. The final product of this project is to bring a classification model able to estimate customer behavior when requesting services of new connections after a energy disconnection using clients features as inputs for model simulation.